2021
DOI: 10.1249/tjx.0000000000000179
|View full text |Cite
|
Sign up to set email alerts
|

Magnesium and Vitamin D Supplementation on Exercise Performance

Abstract: INTRODUCTION MagnesiumMagnesium is the fourth most abundant mineral and the second most abundant intracellular cation in the body, contributing to over 300 metabolic reactions (1). This essential nutrient is involved in the synthesis of nucleic acids and proteins, proper bone development, maintenance of electrolyte balance and mineral homeostasis, as well as oxidative, immune, and neuromuscular functions (2). The recommended dietary allowance (RDA) for magnesium in individuals, 14 yr of age and older, is betwe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 55 publications
(134 reference statements)
0
3
0
Order By: Relevance
“…Volpe ( 38 ) stated that the majority of athletes are not meeting the RDA for magnesium. Further, Hunt et al ( 39 ) reported that, although there is a high rate of magnesium supplement use among athletes, magnesium intakes are still inadequate to meet the average requirement.…”
Section: Discussionmentioning
confidence: 99%
“…Volpe ( 38 ) stated that the majority of athletes are not meeting the RDA for magnesium. Further, Hunt et al ( 39 ) reported that, although there is a high rate of magnesium supplement use among athletes, magnesium intakes are still inadequate to meet the average requirement.…”
Section: Discussionmentioning
confidence: 99%
“…Magnesium helps to improve energy levels by raising the ATP availability, which is best defined as the gold energy stores of cells [ 283 ]. Deficiency may cause ATP levels to be depleted, resulting in fatigue and overall reduced performance [ 34 ]. The regular consumption of Mg can improve ATP production, providing athletes with increased energy and improved endurance [ 295 ].…”
Section: Magnesiummentioning
confidence: 99%
“…Low Mg levels may cause ineffective energy metabolism and decreased endurance in individuals who are engaged in a weight training program [ 294 ]. Higher Mg consumption is linked to enhanced cardiorespiratory function and lower oxygen demand during aerobic exercise [ 34 ]. Most studies reported little impact of 500 mg/day Mg on exercise performance in athletes, unless there is a deficit [ 37 , 142 , 296 ].…”
Section: Magnesiummentioning
confidence: 99%
See 1 more Smart Citation